Spanish socio-historical linguistics isolation and contact - Chappell, Whitney; Drinka, Bridget, 1951- (Advances in historical sociolinguistics ;, 2021)
"This interdisciplinary volume explores the unique role of the sociohistorical factors of isolation and contact in motivating change in the varieties of Spanish worldwide. Recognizing the inherent intersectionality of social and historical factors, the book's eight chapters investigate phenomena ranging from forms of address and personal(ized) infinitives to clitics and sibilant systems, extending from Majorca to Mexico, from Panamanian Congo speech to Afro-Andean vernaculars. The volume is particularly recommended for scholars interested in historical linguistics, sociolinguistics, history, sociology, and anthropology in the Spanish-speaking world. Additionally, it will serve as an indispensable guide to students, both at the undergraduate and graduate level, investigating sociohistorical advances in Spanish"--